“Arabic Pop Art” on Instagram: Questioning the Representations of Arabness and Khaleejiness in Digital Art - Clio Chaveneau (Arabian Humanities)
Instagram, the second most widely used social networking platforms in the world, is a privileged place for artists and art lovers to showcase artworks and visual content to a larger audience. In the Middle East and North Africa region, one Instagram account, @arabic.pop.art, currently gathers 399,000 followers by reposting daily various forms of digital work produced in the region. Based on the analysis of all the posts published there from March 2019 to March 2020, I discuss the important presence of Gulf citizens and residents among both the artists and the followers of this Instagram account and how Arab and gulfic/khaleeji symbols, icons and consumerist items are being used in the published artworks. Through its content and given its popularity, this account is actively participating in highlighting Arab youth pop culture and shaping representations of Arab and regional identities (Arabness and Khaleejiness).